Insecta - Diptera - Cuterebridae (Cutiterebridae). - Guimarães, José Henrique (Museu Paraense Emilio Goeldi, 2011)
Brazilian Amazonia has 11 species of Cuterebridae, distributed in 4 genera, representing almost 44% of the South American species of the family.